Does the financial distress matters on manufacturing firms? - Susandya, Anak Agung Putu Gede Bagus Arie; Putra, Gde Bagus Brahma (Institute of Computer Science (IOCS), 2024)
This study aims to analyze the influence of corporate governance mechanisms, liquidity, leverage, and company size on financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange in 2019-2021. The samples in this study were 216 manufacturing companies. The method of determining the sample in this study is using a purposive sampling method. The analysis technique used is logistic regression. The independent variable in this study is the corporate governance mechanism which is proxied by institutional ownership, independent commissioners, audit committees and liquidity, leverage and firm size, while the dependent variable is financial distress. The results of this study indicate that the variable institutional ownership has a negative effect on financial distress, leverage has a positive effect on financial distress while independent commissioners, audit committees, liquidity and firm size have no effect on financial distress